Lost in space [videorecording (DVD)] - Hopkins, Stephen, 1959-; Oldman, Gary; Hurt, William; LeBlanc, Matt; Rogers, Mimi; Graham, Heather, 1970-; Chabert, Lacey, 1982-; Harris, Jared, 1961- (New Line Home Video, 1998)
The Robinson family was going into space to fight for a chance for humanity; now they are fighting to live long enough to find a way home.